Galeni In Hippocratis Epidemiarum librum VI commentariorum I–VIII versio Arabica (Corpus Medicorum Graecorum – Supplementum Orientale, 2022)
The present volume offers the first critical edition of the medieval Arabic translation of Galen's Commentary on Book 6 of the Hippocratic Epidemics. It is the sequel to the previous editions of Galen's Commentary. The Arabic text is accompanied by an English translation and extensive indices. The introduction outlines the history of the Greek and Arabic text of the commentary and discusses authorship, dating and style of the Arabic translation.